Combine harvesting efficiency as affected by rice field size and other factors and its implication for adoption of combine contracting service. (2nd January 2019) - Xangsayasane, Phetmanyseng; Phongchanmisai, Senthong; Bounphanousai, Chay; Fukai, Shu
ABSTRACT: Small combine harvesters have become popular in SE Asia recently, but small rice fields appear to limit its field operation and hence its wide adoption by smallholders. Combine harvesting efficiency, the area of paddy field harvested per unit time, was determined for 6 seasons in Central Lao PDR for over 400 fields varying in size and toposequence position, rice varieties grown, crop establishment methods and crop conditions particularly lodging at harvest. Combine harvesting efficiency was commonly about 3 ha/day in small fields of less than 1000 m 2 and increased with the increase in field size up to 5 ha/day in the size of about 2000–3000 m 2, but not beyond this range. Lower efficiency was also found in wet season than dry season, and also crops established from broadcasting compared with transplanting and drill seeding, at least partly because broadcasted crops tended to lodge more often than crops established from other methods. Photoperiod sensitive, long duration varieties grown in lower field positions also tended to have lower combine efficiency. Using the data obtained in this work, net return of combine adoption to farmers was estimated for different combine charge fees and yield levels. Increasing combine harvesting efficiency by 50% with increased field size would increase the net income of combine harvesting contractors by around 50% at current charges, allowing them to reduce the combine harvesting fees they charge. This would aid the adoption of combine harvesting services.